The Role of Artificial Intelligence in the Diagnosis and Management of Ischemic Stroke in Indonesia: A Systematic Review - Sumardi, Fitri Sepviyanti (Faculty of Medical - UPN Veteran Jawa Timur, 2025)
Background: Ischemic stroke is a leading cause of death and disability in Indonesia. However, with the emergence of artificial intelligence (AI), there is a promising future for improving stroke diagnosis and management. This article aims to explore the potential of AI in this context, as well as the challenges and opportunities for its implementation in Indonesia, offering a hopeful outlook for the future of stroke care. Article Selection Methodology: This is a narrative study on the utilization of AI in diagnosing and managing ischemic stroke. Using the keywords' role of AI in diagnosing and managing ischemic stroke,' we retrieved and critically reviewed approximately 16 relevant articles from PubMed, Scopus, and Google Scholar. Results: Artificial intelligence (AI) presents a promising avenue for enhancing stroke diagnosis. Its ability to analyze data faster and more accurately and to assist medical personnel in making better clinical decisions is a significant advancement. However, it's crucial to recognize and address challenges, such as the need for high-quality data and adequate user training. Overcoming these hurdles is critical and requires our utmost determination and commitment to fully realizing the potential of AI in daily clinical practice. Conclusion: Artificial intelligence has significant potential in diagnosing and managing ischemic stroke in Indonesia. Its ability to enhance diagnostic accuracy, streamline clinical decision-making, and improve access to care is undeniable. However, to fully realize these benefits, we must urgently invest in further research and foster collaboration among various stakeholders. We can ensure the safe, effective, and ethical implementation of this transformative technology through these concerted efforts.